PENGENALAN DAN PEMBERIAN TERAPI KOMPLEMENTER BEKAM PADA LANSIA DI DESA PILANGPAYUNG - Wahyu Riniasih; Farhan Muhammad Naji; Wahidah Nur Khasana; Abdul Rasyid Ariadi; Tika Dwi Ningrum; Festy Mahanani Mulyaningrum; Muhammad Makmun; Rahmawati; Suryani; Purhadi; Risti Linta Chumaira (LPPM AN Nuur, 2025)
Background: Complementary cupping therapy also known as cupping therapy, is a traditional healing practice that has been used for thousands of years in various cultures. In fact, there are still many people who are not yet familiar with and can experience complementary cupping therapy directly.Objective: The aim of this community service is to provide an introduction, understanding and experience to the people of Cepaka Village regarding complementary therapies, especially cupping therapy, as an effort to improve the quality of life of the communityMethod: This activity uses a Community-Based Participatory approach. The implementation took place in Pilangpayung Village, Toroh District, Grobogan Regency for 1 days, namely 8 February 2024. There were 9 participants.Results: The level of community knowledge before being given counseling had an average score of 70 and after being given counseling had an average score of 90. 83% of participants felt satisfied and there were changes after therapy.Conclusion: There was an increase in community knowledge after counseling and some Most people are satisfied with complementary cupping therapy services.K